Improving insulation in metakaolin based geopolymer: Effects of metabauxite and metatalc. (May 2019) - Zenabou, Ngouloure N.M.; Benoit-Ali, Nait; Zekeng, S.; Rossignol, S.; Melo, U.C.; Tchamba, A.B.; Kamseu, E.; Leonelli, C.
Abstract: To improve the thermal stability of porous geopolymers, metabauxite and metatalc were used as partial replacement of metakaolin. The results of optical microscopy, Scanning Electron Microscopy (SEM), thermal sintering, mercury intrusion porosimetry (MIP) and hot disk investigations, were used to establish the effective stability of the porous composites up to 800 °C. At 1000 °C, the metabauxite based composites showed microcracks into the larger pores and small microcracks into the matrix as the results of residual poorly bounded Alumina oligomers. Metatalc based porous composites showed microcracks only inside larger pores. Those microcracks can be eliminated with the optimization of the mix-design. Despite those microcracks, the specimens maintained their integrity and stability. Above 800 °C it can be seem that the thermal conductivity of the matrices with only metakaolin increases more rapidly compared to matrices containing metatalc or metabauxite. The combination of high volume of porosity (60–65%), low thermal conductivity ( ̴ 0.30 W/m/K) and good thermal stability gives to porous refractory geopolymers a large scale of intrinsic properties that can be positively exploited in the field of incinerators, anti flames, kilns and building constructions. Graphical abstract: fx1 Highlights: Metabauxite and metatalc induced the crystallization of kalsilite and cordierite respectively in porous K-geopolymers. The extent of crystallization modified the thermal stability and thermal transport behaviour of porous K-geopolymers. Thermal stability and homogeneous pores distribution allowed to correlate the effective thermal conductivity with porosity up to 1000 °C; in line with the Maxwell-Eucken and EMPT analytical models.